Odsev globalnih družbenih sprememb na vsebino regionalnega prostorskega planiranja - Ravbar, Marjan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1997)
Following the short overview of socioeconomic changes and developmental stages of regional spatial planning in Slovenia after the 2nd World War, the paper discusses the methodological approaches in regional spatial planning.
Keywords: družbene spremembe; ekonomski razvoj; prostorsko planiranje; regionalno planiranje; Slovenia; Slovenija; spatial planning